2007
DOI: 10.1136/sti.2007.027060
|View full text |Cite
|
Sign up to set email alerts
|

Home-based versus clinic-based self-sampling and testing for sexually transmitted infections in Gugulethu, South Africa: randomised controlled trial

Abstract: Objectives: To test whether more women are screened for sexually transmitted infections when offered homebased versus clinic-based testing and to evaluate the feasibility and acceptability of self-sampling and selftesting in home and clinic settings in a resource-poor community. Methods: Women aged 14-25 were randomised to receive a home kit with a pre-paid addressed envelope for mailing specimens or a clinic appointment, in Gugulethu, South Africa. Self-collected vaginal swabs were tested for gonorrhoea, chla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 12 publications
9
77
0
Order By: Relevance
“…Analysis of self-sampled cervicovaginal lavage specimens resulted in comparable numbers of hr-HPV detection and showed similar sensitivity compared to gynecologist-taken samples. These results are in line with previous studies that compared self-and clinician-collected specimens to identify women with a risk of high-grade CIN and cervical precancer (3,5,8,9,10,15). In our study, the self-sampling method was used for the first time in a cross-sectional approach to determine HPV prevalence and genotyping and not to determine a clinical outcome.…”
Section: Discussionsupporting
confidence: 78%
“…Analysis of self-sampled cervicovaginal lavage specimens resulted in comparable numbers of hr-HPV detection and showed similar sensitivity compared to gynecologist-taken samples. These results are in line with previous studies that compared self-and clinician-collected specimens to identify women with a risk of high-grade CIN and cervical precancer (3,5,8,9,10,15). In our study, the self-sampling method was used for the first time in a cross-sectional approach to determine HPV prevalence and genotyping and not to determine a clinical outcome.…”
Section: Discussionsupporting
confidence: 78%
“…However, analysis of acceptability subscale scores showed that participants perceived self-testing for trichomoniasis as more comfortable than clinician testing, were less confident of their ability to collect/perform the test, and trusted the results less than clinician testing. Two other studies have assessed acceptability of self-testing for STIs 28 29. Adult women in South Africa were randomised to home testing versus clinic-based testing for STIs.…”
Section: Discussionmentioning
confidence: 99%
“…One of these also included school-based implementation for more than half of the study subjects; however, stratified data were not provided, so we were unable to select the non-school-related data of interest to this review. Another two examined outreach strategies, but recruitment into the study depended on and started with health facility access [42,45].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Twenty-one studies describing results of out-of-facility delivery of health services to youth or populations including youth were excluded (Table 1) [27,30,33,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]; 15 studies were excluded because none of this review's outcomes of interest were measured in those studies. Another three were excluded because the studies did not meet eligibility based on this review's age-ofsubjects criteria.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%